Restruksi* Estetika dalam Wujud Kosakarya Seni - Toekio, Soegeng (KEMADHA, 2011)
When people looked at clouds of dark clouds, people will assume that the rain will soon arrive; cloudy become markers hujan. Like markers that deliver meaning and we agree on the truth. In the scope of visual arts, certainly not that simple to get the meaning of a perupaan. Various backgrounds on the following concepts of media used to be a differentiator . Kekaryaan or even the perpetrators are often targeted for a review and make conversation material. There was dialogue about the work & perupanya, about the work and its economic impact, and so on. Unfortunately, however , is there any dialogue to dissect karyarupa tradition for entries art of science? Yes maybe one or two of limited community can only be done, but the portion that is oriented towards more macro may need to be our concern.In the atmosphere created by dualism mainstream of the developing nations, will require many wise minds to be able to form a renewal without any cultural conflict. Negative picture of the atmosphere that can only be a source of catastrophe for the existence of cultural assets that no longer have a place to exist. However , it does not mean that the old habits that rests on peradatan was then terluluhkan. Actually there are superior power of indigenous culture (ethnicity) and has a strong desire to keep strong in the midst of a global culture. Excellence that has been proven true history has shown its reputation and acknowledged able to appear in the middle of chess world. Some are even no longer something that is familiar , such as: woven, batik, wayang, gamelan, keris / tosanaji, weaving, grabah, and other kria products using natural ingredients.Exposure will be delivered is actually trying to look fragments of artistic assets are spread widely in the country ini.Saya believe there are enough young researchers who explored it and make a review about it. However , what is produced is still not supported by preaching and caring for the other party can strengthen its contribution to the science of our art.